2016
DOI: 10.1186/s13033-016-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of perinatal mental disorders in rural, predominantly ethnic minority communities in northern Vietnam

Abstract: BackgroundPreliminary research has suggested that perinatal mental disorders (PMDs), including post-partum depression, are prevalent in Vietnam. However the extent to which these disorders are recognized at the community level remains largely undocumented in the literature. PMDs have also never been investigated within Vietnam’s significant ethnic minority populations, who are known to bear a greater burden of maternal and infant health challenges than the ethnic majority.ObjectiveTo investigate knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 26 publications
3
25
0
1
Order By: Relevance
“…Pregnant women have difficult relationships with their partners because of men's alcohol consumption [15]. Use of alcohol can lead to inappropriate behaviour among men, such as interpersonal violence in the form of verbal abuse when quarrelling, which may influence EMs' mental well-being [28]. In Thailand, it has been found that many pregnant women (> 60%) drink alcohol and stop when they get pregnant, and more than 50% of pregnant women have low marital satisfaction with their husbands [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women have difficult relationships with their partners because of men's alcohol consumption [15]. Use of alcohol can lead to inappropriate behaviour among men, such as interpersonal violence in the form of verbal abuse when quarrelling, which may influence EMs' mental well-being [28]. In Thailand, it has been found that many pregnant women (> 60%) drink alcohol and stop when they get pregnant, and more than 50% of pregnant women have low marital satisfaction with their husbands [6].…”
Section: Discussionmentioning
confidence: 99%
“…Having a conflict with the parentsin-law has been associated with antenatal depression in Asian cultures [5], e.g. in Vietnam [28]. It is a cultural norm that women in north-eastern Thailand move to their in-law family after marriage, and after childbirth most women (87%) mainly take care of their children [13].…”
Section: Discussionmentioning
confidence: 99%
“…Ainda no Vietnã, Daniel Abrams et al (2016) realizaram pesquisa qualitativa em quatro comunidades rurais com minorias étnicas. As entrevistas foram conduzidas tendo dois casos como mote (um caso de depressão pós-parto e outro de ansiedade generalizada).…”
Section: Resultsunclassified
“…In a Japanese study, Ozeki et al [82] observed HLA-A*31:01 was present in 37 of 61 patients with SCARs, significantly higher than in the general population (OR, 10.8; 95% CI, 5.9–19.6). Similarly, McCormack et al found in Europeans that HLA-A*31:01 was associated with all types of CBZ-induced SCARs in SJS (OR, 25.93; 95% CI, 4.93–116.18) and HSS (OR, 12.41; 95% CI, 1.27–121.03) [85]. In contrast, studies in Canada [86], Korea [83] and Taiwan [74], have confirmed HLA-A*31:01 is a genetic risk factor for only non-bullous skin reactions such as HSS and MPE, and not for SJS/TEN [69].…”
Section: Hla and Severe Cutaneous Adverse Drug Reactionsmentioning
confidence: 89%